Approaches to discourse analysis - Gordon, Cynthia, 1975- (Georgetown University round table on languages and linguistics series (2004), 2021)
"Approaches to Discourse Analysis lends insights into micro-linguistic strategies, multimodality, meaning making, relationship and identity negotiation, ideological constructions, cultural practices, and our social worlds. The approaches employed in the eleven chapters are qualitative and quantitative; involve categorizing tokens and turn-by-turn analysis; use a range of transcription conventions; analyze speech, embodied communication, and online texts and images; differently rely on ethnographic and participants' own interpretive insights; and differ in myriad other subtle and not-so-subtle ways. The chapters analyze discourse in multiple languages, across multiple contexts, and in multiple modes. Collectively, they highlight the diversity and complexity of the field in terms of methods of data collection, topical foci, and analytic procedures, while emphasizing a unified goal of understanding communication as fundamentally connected to human agency and creativity, as co-constructed, and as embedded in and constitutive of our social and cultural worlds. Approaches to Discourse Analysis demonstrates the importance of the diverse perspectives that various approaches to discourse bring to bear on human communication, while also providing readers a window to the branches of our discipline, and how they diverge, intertwine, and blossom"--